ULTRASOUND DIAGNOSIS OF CHOLEDOCHAL CYST - Idrees, Mohammad (Journal of Ayub Medical College Abbottabad, 1996)
Choledochal cyst is an aneurysmal dilatation of the common bile duct, supraduodenal part being the commonest site. Female predominate with female to male ratio of 4:1. It is more common in oriental races, particularly in Japan. The anomaly is rarely seen in Europe 1 . We submit two cases of choledochal cyst which were diagnosed by ultrasound